‘A seat at the table’: spaces of activism in the development of LGBTQ rights in Northern Ireland - Harsant, Rosie (2019)
This study explores the spaces of sexual politics within Northern Ireland, through examining the spaces and strategies of activists. Geographers who study sexuality understand the spatially varied nature of sexual politics, and how this can be shaped by forms of activism. This research uses scholarship from political geography and the geographies of sex and sexuality to examine activist spaces, and how they may reproduce homonormativity and ‘heteroactivism’. With a particular focus on parliamentary, online, and urban spaces, this study draws together multiple scales and spaces to understand the geopolitical processes which impact on sexual politics within Northern Ireland. By using the body as a scale and site of performance, I develop an understanding of the uneven geopolitical processes which impact on LGBTQ lives and activism in Northern Ireland. Ultimately, this research demonstrates the complex relationship between scales, spaces, activism, and sexualities.